Internet-Based Brief Intervention to Reduce Alcohol Consumption in College Students: An Exploratory Randomized Clinical Trial. - Romero Reyes, Daniela; Moriano León, Juan Antonio; Ybarra Sagarduy, José Luis (Salud Mental)
Introduction: Hazardous alcohol consumption among university students is a public health issue, which theoretically supported internet-based interventions have proven effective in addressing. Objective: To evaluate the effectiveness of an internet-based brief intervention, registered at clinicaltrials.gov as NCT05533554. The intervention was designed using the Theory of Planned Behavior (TPB), based on the hypothesis that alcohol consumption intention and drinking behavior will be lower in the experimental group compared to the control group. Method: An experimental design was employed, including an experimental group (n = 38) and a control group on a waiting list (n = 38), with pre- and post-intervention evaluations conducted a month apart. The control group consisted of 36 participants at the time of receiving the intervention. Results: The intervention reduced the number of drinks per occasion in the experimental group. Monthly consumption, number of drinks per occasion, and days of consumption decreased in the at-risk subgroup. The descriptive norm in the experimental group decreased, suggesting that addressing social norms may be related to behavioral changes. The intervention in the control group increased self-efficacy in coping with potential alcohol abuse situations. Discussion and conclusion: The internet-based brief intervention was effective in reducing alcohol consumption in the experimental group, particularly the at-risk subgroup. The control group's self-efficacy in dealing with alcohol abuse also increased following the intervention. Further experimental studies are recommended to confirm its effectiveness.